MicroRNAs in gynecological cancers: Small molecules with big implications. (28th October 2017) - Srivastava, Sanjeev K.; Ahmad, Aamir; Zubair, Haseeb; Miree, Orlandric; Singh, Seema; Rocconi, Rodney P.; Scalici, Jennifer; Singh, Ajay P.
Abstract: Gynecological cancers (GCs) are often diagnosed at advanced stages, limiting the efficacy of available therapeutic options. Thus, there remains an urgent and unmet need for innovative research for the efficient clinical management of GC patients. Research over past several years has revealed the enormous promise of miRNAs. These small non-coding RNAs can aid in the diagnosis, prognosis and therapy of all major GCs, viz., ovarian cancers, cervical cancers and endometrial cancers. Mechanistic details of the miRNAs-mediated regulation of multiple biological functions are under constant investigation, and a number of miRNAs are now believed to influence growth, proliferation, invasion, metastasis, chemoresistance and the relapse of different GCs. Modulation of tumor microenvironment by miRNAs can possibly explain some of their reported biological effects. miRNA signatures have been proposed as biomarkers for the early detection of GCs, even the various subtypes of individual GCs. miRNA signatures are also being pursued as predictors of response to therapies. This review catalogs the knowledge gained from collective studies, so as to assess the progress made so far. It is time to ponder over the knowledge gained, so that more meaningful pre-clinical and translational studies can be designed to better realize the potential that miRNAs have to offer. Highlights: miRNAs affect proliferation, survival, metastasis and chemoresistance of gynecological cancers. miRNAs regulate the tumor microenvironment of gynecological cancers. miRNAs are novel diagnostic and prognostic markers for individual gynecological cancers and their subtypes.